The Relevance of Applying the Rule of Reason in Analyzing Alleged Interest Rate Cartels in Fintech Lending under Article 5 of Law No. 5 of 1999 - Arvinci Ngabut, Rupertus; C. Adam, Richard (Universitas Islam Negeri Alauddin Makassar, 2026)
The rapid growth of the financial technology (fintech) industry has spurred the emergence of alternative financing models through peer-to-peer (P2P) lending services in Indonesia. This innovation plays a crucial role in expanding access to financing and enhancing financial inclusion; however, it has also raised legal concerns, particularly regarding potential cartel practices in interest rate setting by operators affiliated with the Indonesian Joint Fintech Funding Association (AFPI). This study aims to analyze the relevance of applying the rule of reason approach in assessing alleged interest rate cartel practices in the fintech lending industry, as well as to evaluate to what extent this approach can reflect a balance between economic efficiency and the protection of business competition as stipulated in Article 5 of Law No. 5 of 1999. This study employs a normative legal methodology using legislative, case-based, and conceptual approaches. Previous research on competition compliance in the fintech sector has generally focused on the effectiveness of the KPPU’s compliance programs and the supervisory role of the OJK; however, it has not specifically examined interest rate standardization by industry associations within the framework of the rule of reason. In this context, the application of the rule of reason becomes crucial and context-specific, as the uniformity of interest rates facilitated by the AFPI under OJK supervision cannot automatically be classified as a violation of competition law if it is proven to enhance efficiency, reduce credit risk, and protect consumers. Thus, this study contributes a critical analysis of the relationship between fintech sectoral regulation, the role of industry associations, and the potential for price cartels from a competition law perspective, while reinforcing the urgency of integrating economic analysis into competition law enforcement in the digital sector.